Relationship between Authoritarian Parents and Student Dicipline - Lidya Puspita Sari; Yusri Yusri (Universitas Negeri Padang, 2019)
Authoritarian parenting is characterized by the characteristics of the attitude of parents who are rigid and hard in applying the rules and discipline, the discipline will be realized through coaching from an early age, since young, starting from the family environment through education that is embedded from a young age which is increasingly united in themselves with increasing age, therefore in addition to getting fostered from school most parents use an authoritarian parenting pattern to foster and educate child discipline early on. This study aims to examine the relationship of authoritarian parenting with student discipline. This research is a descriptive correlational research with quantitative methods. Sampling in this study used stratified random sampling with a sample of 216 students. The research instrument used was a questionnaire for parental authoritarian parenting and student discipline. The results showed that (1) parenting mostly tends to apply authoritarian parenting (2) there is a positive relationship between parental authoritarian parenting with student discipline.